Classifying closed and open skills and their effect on acquisition and maintaining the level of performance of some handball skills - Abdulhameed, Noor Dheyaa (International Journal of Psychosocial Rehabilitation, 2020)
The researcher used the experimental method for its suitability and the nature of the research. The research was conducted on a sample of (24) students from the second phase of the College of Physical Education / out of (70) male and female students from the research community. The sample was divided into two equal experimental groups by (12) students for each group. The first experimental group applied the method of serial exercise scheduling, while the second experimental group applied the method of random exercise scheduling, homogeneity and parity were achieved for the two groups in the variables of age, height and weight and some basic handball skills. The researcher used the design of the random selection group with equal pre and post testing, and the two educational programs were prepared to acquire and retain some basic handball skills, as the handling and receiving skills were classified into open skills, while the skills of typing and correction were classified on the basis of closed skills.The implementation of the proposed educational program took (6) weeks, with two educational units per week. Thus, the number of educational units reached (12) educational units for each experimental group to acquire and retain some basic skills in handball (handling - receiving - cheating - correction) and the program was implemented for a period of 15/ 3/2019 until 3/5/2019After data collection, it was statistically processed using (arithmetic mean, median, standard deviation, torsional coefficient, test (t) of two interconnected and unrelated and equal arithmetic mean) and the results were treated using the spss system